Implementation of Zakat Funds in Seeking Economic Improvement in Medan City - Junnanda Junnanda; Tri Inda Fadhila Rahma (Penerbit Jurnal Indonesia, 2022)
The purpose of this study is to find out how zakat funds seek to improve the economy in the city of Medan. In this study using qualitative research methods with data collection taking from accurate sources such as previous journals and books that discuss zakat. The results of the study show that the empowerment of zakat funds in economic growth in the city of Medan is very good and properly managed by the Amil Zakat Institute (LAZ) in the city of Medan.